Upaya Peningkatan Pengetahuan dan Keterampilan dalam Penanganan Pertama pada Kejang Demam di Posyandu Garuda II Kembaran Purwokerto - Siti Anisa anisa; Rahmaya Nova Handayani; Surtiningsih (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
An important factor in speeding up a child's recovery is the mother's knowledge about her child's illness. A mother must play an important role when her child suffers from a febrile seizure to prevent the child from experiencing more serious health issues. The knowledge that a mother possesses can support the management of the fever condition that occurs. Objective. This Community Service activity aims to help improve knowledge and skills in the first handling of febrile seizures at Posyandu Garuda II Kembaran Purwokerto. Methods. Community service activities are carried out by conducting lectures, implementation and direct evaluation by applying increased knowledge and skills in the first handling of febrile seizures. Results. Based on the results of PkM activities, before being given education there were 8 participants (16.3%) in the good knowledge category, 23 participants (46.9%) in the sufficient knowledge category and 18 participants (36.7%) in the poor knowledge category. Then after being given education using audiovisual and leaflets, there was an increase in knowledge, namely 44 participants (89.8%) in the good knowledge category and 5 participants (10.2%) in the moderate knowledge category. As for the skill level before being given a demonstration, all participants were not skilled. Then after being given demonstrations, audiovisuals and leaflets increased to skillful, namely 37 participants (75.5%) and 12 participants (24.5%) were less skilled. The conclusion is that after being given education there is an increase in knowledge and skills. Keywords: Knowledge; Skills; Fever Seizures;